PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, CORPORATE GOVERNANCE, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Fathia Alifia Tsabita; Marsono Marsono (Diponegoro Journal of Accounting, 2023)
This study examines the relationship between corporate social responsibility disclosure, corporate governance disclosure, and profitability with firm value in manufacturing companies. This study uses firm value as the dependent variable and corporate social responsibility disclosure, corporate governance disclosure, and profitability as independent variables. This study also uses leverage and firm size as control variables. The population in this study are manufacturing companies listed on the Indonesian Stock Exchange within the period of 2017-2021. Using purposive sampling, 93 samples were obtained for 5 consecutive years. This study uses multiple linear regression analysis to test the hypothesis. The finding from this study proves that corporate social responsibility disclosure negatively affects firm value, corporate governance disclosure has positive and significant relationship on firm value, and profitability has no significant relationship on firm value.